Inhibition of malaria and babesiosis parasites by putative red blood cell targeting small molecules - Groomes, Patrice V.; Paul, Aditya S.; Duraisingh, Manoj T. (Frontiers in Cellular and Infection Microbiology, 2024)
Background Chemotherapies for malaria and babesiosis frequently succumb to the emergence of pathogen-related drug-resistance. Host-targeted therapies are thought to be less susceptible to resistance but are seldom considered for treatment of these diseases. Methods Our overall objective was to systematically assess small molecules for host cell-targeting activity to restrict proliferation of intracellular parasites. We carried out a literature survey to identify small molecules annotated for host factors implicated in Plasmodium falciparum infection. Alongside P. falciparum, we implemented in vitro parasite susceptibility assays also in the zoonotic parasite Plasmodium knowlesi and the veterinary parasite Babesia divergens. We additionally carried out assays to test directly for action on RBCs apart from the parasites. To distinguish specific host-targeting antiparasitic activity from erythrotoxicity, we measured phosphatidylserine exposure and hemolysis stimulated by small molecules in uninfected RBCs. Results We identified diverse RBC target-annotated inhibitors with Plasmodium-specific, Babesia-specific, and broad-spectrum antiparasitic activity. The anticancer MEK-targeting drug trametinib is shown here to act with submicromolar activity to block proliferation of Plasmodium spp. in RBCs. Some inhibitors exhibit antimalarial activity with transient exposure to RBCs prior to infection with parasites, providing evidence for host-targeting activity distinct from direct inhibition of the parasite. Conclusions We report here characterization of small molecules for antiproliferative and host cell-targeting activity for malaria and babesiosis parasites. This resource is relevant for assessment of physiological RBC-parasite interactions and may inform drug development and repurposing efforts.